Transformasi kejahatan dari offline menjadi online berbasis media sosial menurut pandangan Al-Qur’an (analisis cyber bullying) - Ramlah, Ramlah; Damanik, Nurliana (Academy of Education Journal, 2024)
The transformation of crime from the offline world to the online world has become a striking phenomenon along with technological developments. Viewing the Qur'an as a source of Islamic teachings provides a valuable perspective in understanding this phenomenon. In this context, this research examines the verses of the Qur'an that are relevant to this problem using ulama's interpretation as a tool for deeper understanding. The Qur'an teaches moral values, ethics and guidelines for Muslims in dealing with the problem of online crime. By referring to verses of the Qur'an such as Surah Al-Hujurat (49:11), Surah Al-Isra' (17:33), Surah Al-Ma'idah (5:38), and Surah An-Nisa (4:29), this research illustrates how the views of the Koran can be applied in maintaining online ethics, avoiding crimes such as cyber bullying, theft and fraud, as well as creating an online environment that is more polite and respectful of others. This research uses a qualitative descriptive approach with an interpretation of the Al-Qur'an, providing insight into moral values that can shape better online behavior in accordance with Islamic teachings